Impact of Risk Associated with Procurement Process on Cost Performance of Public Tertiary Education Institution Projects in Ondo State, Nigeria - B., Fagbemi Kayode (Local Engineering, 2025)
The procurement process remains a critical component in determining the success of construction projects, especially in public institutions. This study evaluates the impact of risks associated with procurement processes on the cost performance of building projects in public tertiary education institutions in Ondo State, Nigeria. Data were gathered from 63 construction projects using structured questionnaires and a pro forma. Analytical tools employed include frequency, mean item score, Paired-Samples T-Test, Shapiro-Wilk Test, Kruskal-Wallis Test, Mann-Whitney U Test, and Cronbach's Alpha. Results revealed a statistically significant difference between initial and final project costs, with major procurement risks identified at the planning, specification, and bid evaluation stages. The study recommends stricter attention to procurement planning and risk assessment to improve cost performance in public building projects.